Facile Synthesis and Optimization of Crooh/Rgo-Based Electrode Material for a Highly Efficient Supercapacitor Device - Serafini, D; Singh, D; Vivas, L; Garcia-Garfido, J (American Chemical Society, 2022)
New electrode materials for supercapacitor devices are the primary focus of current research into energy-storage devices. Besides, exact control of the proportions of these new materials while forming electrodes for coin cell supercapacitor devices is very important for the large-scale manufacturing or at industrial scale. Here we report a facile synthesis of CrOOH with ascorbic acid and explore an exact composition with reduced graphene oxide to achieve a highly efficient electrode material for supercapacitor devices. The rGO is synthesized by modified Hummer s method followed by reduction with ascorbic acid, whereas ultrasmall CrOOH nanoparticles result via hydrothermal treatment of the reactants Cr(NO3)3, NaOH, and ascorbic acid at 120 °C for 12 h. The ultrasmall CrOOH nanoparticles show an amorphous phase with particle size range 3-10 nm and a calculated band gap of 3.28 eV. Six different composites are prepared by varying the proportion of CrOOH and rGO materials and further utilized as active electrode materials for fabrication of the coin cell supercapacitor devices. We report the highest specific capacitance for the 70% CrOOH and 30% rGO composite that exhibits a capacitance of 199.8 mF cm-2with a long cyclic stability up to the tested 10,000 charge/discharge cycles. The proposed supercapacitor device exhibits a high energy and power density of 8.26 Wh kg-1and 3756.9 W kg-1, respectively, at Ragone Plot, showing the commercial viability of the device. © 2022 American Chemical Society. All rights reserved.